Factors associated with patient trust in their clinicians: Results from the Healthy Work Place Study. Issue 4 (17th October 2022) - Khullar, Dhruv; Prasad, Kriti; Neprash, Hannah; Poplau, Sara; Brown, Roger L.; Williams, Eric S.; Audi, Crystal; Linzer, Mark
Abstract : Supplemental digital content is available in the text. Abstract : Background: Patient trust in their clinicians is an important aspect of health care quality, but little evidence exists on what contributes to patient trust. Purpose: The aim of this study was to determine workplace, clinician, and patient correlates of patient trust in their clinician. Methodology/Approach: The sample used baseline data from the Healthy Work Place trial, a randomized trial of 34 Midwest and East Coast primary care practices to explore factors associated with patient trust in their clinicians. A multivariate "best subset" regression modeling approach was used, starting with an item pool of 45 potential variables. Over 7 million models were tested, with a best subset of correlates determined using standard methods for scale optimization. Skewed variables were transformed to the fifth power using a Box–Cox algorithm. Results: The final model of nine variables explained 38% of variance in patient trust at the patient level and 49% at the clinician level. Trust was related mainly to several aspects of care variables (including satisfaction with explanations, overall satisfaction with provider, and learning about their medical conditions and their clinician's personal manner), with lesser association with patient characteristics and clinician work conditions. Conclusion: Trust appears to be primarily related to what happens between clinicians and patients in the examination room. Practice Implications: System changes such as patient-centered medical homes may have difficulty succeeding if the primacy of physician–patient interactions in inspiring patient trust and satisfaction is not recognized.